Crosslinked polyethylene composition for ultrahigh-voltage cable insulation as well as preparation method and application of crosslinked polyethylene composition

By using a specific combination of crosslinked polyethylene compositions in ultra-high voltage cable insulation materials, the risk of creep deformation in long-term high temperature operation is solved, and high operating reliability under ultra-high voltage conditions of 500 kV and above is achieved.

CN119798821APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510002487.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing ultra-high voltage cable insulating materials have a risk of creep deformation during long-term high-temperature operation, and it is difficult to quickly evaluate the relationship between antioxidants and crosslinking agents, which affects the long-term reliability of the cable.

Method used

Using a crosslinked polyethylene composition for ultra-high voltage cable insulation, including low-density polyethylene, specific antioxidant (4,4'-thiobis(6-tert-butyl-3-methylphenol)) and anti-caloric agent (2,4-diphenyl-4-methyl-1-pentene), the anti-aging performance of the material is improved through specific preparation methods and process flows.

Benefits of technology

The anti-aging performance of the crosslinked polyethylene composition is significantly improved, the spline retention time and the start breaking time are extended, and the high operating reliability of the cable under ultra-high voltage conditions of 500kV and above is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225773450000061
    Figure BDA0005225773450000061
  • Figure BDA0005225773450000071
    Figure BDA0005225773450000071
  • Figure BDA0005225773450000081
    Figure BDA0005225773450000081
Patent Text Reader

Abstract

The invention discloses a crosslinked polyethylene composition for ultrahigh-voltage cable insulation as well as a preparation method and application of the crosslinked polyethylene composition. The composition is prepared from the following components in parts by weight: 95 to 100 parts of low density polyethylene, 0.5 to 2.0 parts of a cross-linking agent, 0.1 to 0.5 part of an antioxidant and 0.05 to 0.3 part of an anti-scorching agent, wherein the antioxidant is 4, 4 '-thiobis (6-tert-butyl-3-methylphenol), the chloride ion content of the antioxidant is smaller than or equal to 500 ppm, preferably smaller than or equal to 100 ppm, and the purity of the antioxidant is larger than or equal to 99.5%. The cross-linked polyethylene composition provided by the invention shows excellent performance in a thermal extension test, a cable prepared from the cross-linked polyethylene composition is reliable in long-period operation, and particularly, the cross-linked polyethylene composition can realize high operation reliability in 500kV and above ultrahigh-voltage cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cross-linked polyethylene, in particular to a cross-linked polyethylene composition for ultra-high voltage cable insulation and a preparation method and application thereof. Background Art

[0002] With the advancement of science and technology, the development of industrialization and urbanization requires sufficient electric energy as a strong support and guarantee. Among them, high-voltage and ultra-high-voltage power transmission is becoming more and more important. Cross-linked polyethylene has become the core insulation material of ultra-high voltage cables due to its excellent electrical, mechanical and thermal stability.

[0003] After the high-voltage cable is laid, it is generally necessary to operate for 30-40 years under high temperature conditions of about 90°C. The cable insulation material is close to the softening point for a long time, and there is a risk of creep deformation. In addition, as the conductor cross-section of the cable continues to increase, the weight of the conductor in the cable continues to increase, especially the promotion and application of cables with higher voltage levels, which puts higher requirements on its creep resistance.

[0004] At present, the industry basically uses thermal extension test to evaluate the elongation and permanent deformation rate of cables. It is known that thermal extension can be affected by the combined effect of antioxidants and cross-linking agents, but how to better and faster evaluate the relationship between the two and quickly screen the physical property changes of cables running at 90°C for 30-40 years is still a big challenge. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a cross-linked polyethylene composition for ultra-high voltage cable insulation and a preparation method and application thereof. The cross-linked polyethylene composition provided by the present invention exhibits excellent performance in a hot extension test, and the cable prepared therefrom has long-term reliable operation, especially high operation reliability in ultra-high voltage cables of 500 kV and above.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A cross-linked polyethylene composition for ultra-high voltage cable insulation, comprising the following components in parts by weight:

[0008] 95-100 parts of low density polyethylene (LDPE), such as 95 parts, 96 parts, 97 parts, 97.4 parts, 97.8 parts, 98.0 parts, 98.5 parts, etc.,

[0009] 0.5-2.0 parts of cross-linking agent, such as 0.5 parts, 1.0 parts, 1.5 parts, 2.0 parts, etc.,

[0010] 0.1-0.5 parts of antioxidant, such as 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts,

[0011] 0.05-0.3 parts of anti-scorch agent, such as 0.05 parts, 0.1 parts, 0.2 parts, 0.25 parts, 0.3 parts, etc.;

[0012] Wherein, the antioxidant is 4,4'-thiobis(6-tert-butyl-3-methylphenol), and its chloride ion content is ≤500ppm, preferably ≤100ppm, for example, 1ppm, 5ppm, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, etc., and the purity is ≥99.5%.

[0013] In the present invention, the antioxidant can be directly purchased from commercially available finished products that meet the specifications, or can be synthesized by reference to existing technologies or obtained by distillation and purification of existing products, without any limitation.

[0014] In some preferred examples, the melt index of the low-density polyethylene at 190°C and 2.16 kg is 1.5-2.5 g / 10 min, such as 1.8 g / 10 min, 2.0 g / 10 min, 2.2 g / min, etc.; the density is 0.91-0.93 g / cm 3 , such as 0.915g / cm 3 、0.92g / cm 3 , 0.925g / cm 3 wait.

[0015] Preferably, the low-density polyethylene is selected from one or more of BASF-YPC 2220H, Shenhua Yulin 2220H, Shanghai Petrochemical J182A, Shanghai Petrochemical J182B, and Yanshan Petrochemical LD9202W.

[0016] In some preferred examples, the crosslinking agent is selected from one or more of dicumyl peroxide (DCP), benzoyl peroxide (BPO), di-tert-butyl peroxide (BTBP), and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0017] In some preferred examples, the scorch retarder is selected from one or more of phthalic anhydride, N-dinitrodiphenylamine, N-cyclohexylthiophthalimide, and 2,4-diphenyl-4-methyl-1-pentene, preferably 2,4-diphenyl-4-methyl-1-pentene.

[0018] The present invention surprisingly found in the research that by selecting 4,4'-thiobis(6-tert-butyl-3-methylphenol) with a chloride ion content of ≤500ppm, preferably ≤100ppm as an antioxidant, it is beneficial to greatly improve the anti-aging performance of the cross-linked polyethylene composition, especially when used in combination with 2,4-diphenyl-4-methyl-1-pentene, the anti-aging performance under long-term high temperature testing is particularly improved, and the two have a typical synergistic improvement effect.

[0019] The cross-linked polyethylene composition for ultra-high voltage cable insulation provided by the present invention has a 5A type specimen whose specimen holding time is greater than 130 minutes in a heat extension test (under the conditions of 0.2 MPa and 200° C.) and no specimen breakage occurs.

[0020] The present invention also provides a method for preparing the cross-linked polyethylene composition for ultra-high voltage cable insulation as described above, comprising the following steps:

[0021] 1) Drying the raw materials; fully mixing the antioxidant, low-density polyethylene and anti-scorch agent to obtain a mixture;

[0022] 2) melting the obtained mixture, extruding it, and granulating it to obtain a granular material;

[0023] 3) Drying the pellets, melting the cross-linking agent, mixing them evenly, and drying them to obtain a cross-linked polyethylene composition.

[0024] In some preferred examples, in step 1), the raw materials are mixed using at least one of the following blending equipment: a twin-screw extruder, a reciprocating single-screw extruder, and an internal mixer.

[0025] In some preferred examples, in step 2), the extrusion temperature is 160-200° C., and the main engine speed is 80-140 rpm.

[0026] In some preferred examples, in step 3), the drying temperature of the pellets is 60-80° C., and the drying time is 4-6 hours.

[0027] In some preferred examples, in step 3), the mixing time of the granular material and the cross-linking agent is 15-30 minutes;

[0028] Preferably, in step 3), the drying time is 16-20 hours.

[0029] The present invention also provides an application of the cross-linked polyethylene composition for ultra-high voltage cable insulation as described above or the cross-linked polyethylene composition for ultra-high voltage cable insulation prepared by the method described above in ultra-high voltage cables, especially in ultra-high voltage cables with a voltage level of ≥500kV.

[0030] The cross-linked polyethylene composition for ultra-high voltage cable insulation provided by the present invention has excellent anti-aging performance, can effectively improve the specimen holding time and the initial fracture time in the thermal extension test, and provide more effective guarantee for the long-term reliable operation of the cable. DETAILED DESCRIPTION

[0031] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0032] The main raw material information in the following examples of the present invention is as follows. Unless otherwise specified, other raw materials and reagents can be obtained through general commercial channels.

[0033] LDPE-1: Low-density polyethylene, Shanghai Petrochemical J182B, melt index is 2.0g / 10min (190℃, 2.16kg), density is 0.922g / cm 3 ;

[0034] LDPE-2: low-density polyethylene, Shenhua Yulin 2220H, 1.8g / 10min (190℃, 2.16kg), density 0.922g / cm 3 ;

[0035] LDPE-3: Low-density polyethylene, Yanshan Petrochemical LD9202W, 2.2g / 10min (190℃, 2.16kg), density 0.922g / cm 3 ;

[0036] Cross-linking agent DCP: dicumyl peroxide, Nouryon, purity 99.0%;

[0037] Cross-linking agent BTBP: diisopropyl tert-butyl peroxide, Nouryon, purity 98%;

[0038] Antioxidant 1: Antioxidant 300, purity 99.5%, chloride ion content 55ppm; Zibo Vanke Chemical Co., Ltd.

[0039] Antioxidant 2: Antioxidant 300, purity 99.5%, chloride ion content 112ppm; Zibo Vanke Chemical Co., Ltd.

[0040] Antioxidant 3: Antioxidant 300, purity 99.5%, chloride ion content 477ppm ; Zibo Vanke Chemical Co., Ltd.;

[0041] Antioxidant 4: Antioxidant 300, purity 99.5%, chloride ion content 823ppm; SI Group;

[0042] Antioxidant 5: Antioxidant 300, purity 99.5%, chloride ion content 1081ppm; Jiangsu Xinluda;

[0043] Scorch retarder 1: 2,4-diphenyl-4-methyl-1-pentene, TCI, purity 99.0%;

[0044] Anti-scorch agent 2: phthalic anhydride, Jiangsu Bosite Chemical Technology Co., Ltd., purity 95%;

[0045] Anti-scorch agent 3: N-cyclohexylthiophthalimide, Shanghai Titan Technology Co., Ltd., purity 99%.

[0046] [Examples 1-6 and Comparative Examples 1-3]

[0047] The raw materials were prepared according to the components and contents (parts by weight) described in the following Table 1, and the cross-linked polyethylene composition was prepared according to the following method:

[0048] 1) Drying the raw materials; fully mixing the antioxidant, low-density polyethylene and anti-scorch agent in an internal mixer to obtain a mixture;

[0049] 2) The obtained mixture is melted and extruded, and the temperature of each section of the extruder is: the temperature of the first zone is 160°C, the temperature of the second zone is 180°C, the temperature of the third zone is 190°C, the temperature of the fourth zone is 200°C, the temperature of the fifth zone is 200°C, and the main engine speed is 100rpm, and then granulation is performed to obtain granular materials;

[0050] 3) The pellets are dried at 60° C. for 4 hours, the cross-linking agent is melted and mixed with the pellets for 30 minutes until the mixture is fully mixed, and then dried for 20 hours to obtain a cross-linked polyethylene composition.

[0051] Table 1

[0052]

[0053]

[0054] The test methods involved in the cross-linked polyethylene composition of the present invention are:

[0055] (1) Long-term high temperature test

[0056] Referring to GB / T 2951.21 and GB / T 1040.2, the specimen is directly molded and vulcanized at 175℃ and 15Mpa for 15min, the type is 5A specimen, the test temperature is 200±3℃, the specimen thickness is 1.0±0.1mm, and a load of 0.2MPa is applied below the specimen. The time from the start of the test to the spline breaking is the spline holding time, and the average value of each group of 5 splines is taken as the spline holding time of the sample; at the same time, the spline breaking time is recorded.

[0057] (2) Air heat aging test of insulation layer chips after cabling

[0058] First, the following three materials were co-extruded using the Telester extruder CCV cross-linking line (cross-sectional area 400mm 2 ), and vulcanize by heating at 380-310℃ in a nitrogen atmosphere to prepare the cable. The cable preparation standard reference: GB / T 12706 or GB / T 11017 standard.

[0059] The flaking test after cabling shall be carried out in accordance with the provisions of GB / T 2951.12 and Q / GDW 11883.2-2018. The air heat aging oven shall comply with the requirements of GB / T 2951.12. The tensile strength and elongation at break tests after heat aging shall be carried out in accordance with the regulations. The aged specimens shall be conditioned for no less than 17 hours in an environment with a temperature of 23±3℃ and a relative humidity of 50±5%.

[0060] The test results of the cross-linked polyethylene compositions in Examples 1-5 and Comparative Examples 1-3 are shown in Table 2:

[0061] Table 2

[0062]

[0063] It can be seen from the test results in Table 2 that the cross-linked polyethylene compositions obtained in Examples 1-4 of the present invention have significantly extended spline retention time and initial break time, and the spline has excellent thermal aging resistance, with only a small change in tensile strength and elongation at break after long-term treatment under high heat conditions.

[0064] Examples 5 and 6 also have extended spline retention time, but the initial break time is shorter than that of Example 3, indicating that the use of 2,4-diphenyl-4-methyl-1-pentene as a scorch retarder has a significant benefit effect on improving the thermal aging properties of the cross-linked polyethylene composition of the present invention.

[0065] Comparison between Example 3 and Comparative Examples 1 and 2 shows that when the chloride ion content in the antioxidant exceeds the limit of 500 ppm, the specimen holding time and the initial breaking time are significantly shortened, and the tensile strength and elongation at break change greatly after long-term treatment under high heat conditions, resulting in serious performance loss.

[0066] Comparison between Example 3 and Comparative Example 3 shows that when no scorch retarder is added, the time when the spline starts to break is seriously advanced, and the spline retention time is also shortened to a certain extent, and the mechanical properties of the material are seriously lost.

[0067] The above shows that the cross-linked polyethylene composition for ultra-high voltage cable insulation provided in the present invention has excellent anti-aging properties. The addition of a specific antioxidant and an anti-scorch agent preferably with a low chloride ion content can effectively improve the batch production cycle of the compound, extend the continuous production capacity during cable extrusion, and enhance the long-term operation reliability of the cable, so as to achieve stable use on ultra-high voltage cables of 500 kV and above.

[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A cross-linked polyethylene composition for ultra-high voltage cable insulation, characterized in that: According to weight parts, it contains the following components: 95-100 parts of low density polyethylene, 0.5-2.0 parts of cross-linking agent, 0.1-0.5 parts of antioxidant, 0.05-0.3 parts of anti-scorch agent; Wherein, the antioxidant is 4,4'-thiobis(6-tert-butyl-3-methylphenol), the chloride ion content of which is ≤500ppm, preferably ≤100ppm, and the purity is ≥99.5%.

2. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to claim 1, characterized in that: The low-density polyethylene has a melt index of 1.5-2.5 g / 10 min at 190° C. and 2.16 kg, and a density of 0.91-0.93 g / cm 3 ; Preferably, the low-density polyethylene is selected from one or more of BASF-YPC 2220H, Shenhua Yulin 2220H, Shanghai Petrochemical J182A, Shanghai Petrochemical J182B, and Yanshan Petrochemical LD9202W.

3. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to claim 1 or 2, characterized in that: The cross-linking agent is selected from one or more of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

4. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to any one of claims 1 to 3, characterized in that: The scorch retarder is selected from one or more of phthalic anhydride, N-dinitrodiphenylamine, N-cyclohexylthiophthalimide, and 2,4-diphenyl-4-methyl-1-pentene, preferably 2,4-diphenyl-4-methyl-1-pentene.

5. A method for preparing a cross-linked polyethylene composition for ultra-high voltage cable insulation according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Drying the raw materials; fully mixing the antioxidant, low-density polyethylene and anti-scorch agent to obtain a mixture; 2) melting the obtained mixture, extruding it, and granulating it to obtain a granular material; 3) Drying the pellets, melting the cross-linking agent, mixing them evenly, and drying them to obtain a cross-linked polyethylene composition.

6. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to claim 5, characterized in that: In step 1), the raw materials are mixed using at least one of the following blending equipment: a twin-screw extruder, a reciprocating single-screw extruder, and an internal mixer.

7. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to claim 5 or 6, characterized in that: In step 2), the extrusion temperature is 160-200° C. and the main machine speed is 80-140 rpm.

8. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to any one of claims 5 to 7, characterized in that: In step 3), the granular material is dried at a temperature of 60-80°C and a drying time of 4-6 hours.

9. The cross-linked polyethylene composition for ultra-high voltage cable insulation according to any one of claims 5 to 8, characterized in that: In step 3), the mixing time of the granular material and the cross-linking agent is 15-30 minutes; Preferably, in step 3), the drying time is 16-20 hours.

10. Use of the cross-linked polyethylene composition for ultra-high voltage cable insulation according to any one of claims 1 to 4 or the cross-linked polyethylene composition for ultra-high voltage cable insulation prepared by the method according to any one of claims 5 to 9 in ultra-high voltage cables, especially in ultra-high voltage cables with a voltage level of ≥500 kV.